Composite solid electrolyte with high ionic conductivity
By using composite materials of modified polyethylene oxide, modified LiFePO4/C and molybdenum dioxide, the problem of low ionic conductivity of polymer solid electrolytes is solved, high ionic conductivity is achieved and the energy density and safety of the battery is improved.
Patent Information
- Application Number
- CN202510022007.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
AI Technical Summary
Existing polymer solid electrolytes have low ionic conductivity, and doping inorganic fillers or liquid electrolytes will affect safety.
The ionic conductivity of the solid electrolyte is improved by ball milling and hot pressing treatment using a composite material of modified polyethylene oxide, modified LiFePO4/C and molybdenum dioxide.
A composite solid electrolyte with high ionic conductivity is achieved, with an ionic conductivity of up to 5.4×10-4S·cm-1, improving the energy density and safety of the battery.
Smart Images

Figure BDA0005231655140000041 
Figure BDA0005231655140000131 
Figure BDA0005231655140000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a composite solid electrolyte with high ionic conductivity. Background Art
[0002] Solid-state batteries are batteries that use solid electrodes and solid electrolytes. Compared with the widely used organic electrolyte lithium-ion batteries, solid-state batteries do not contain liquid electrolytes, thus avoiding the occurrence of leakage and other problems, making solid-state batteries safer. In addition, the core advantage of solid-state batteries lies in their high energy density, which can theoretically reach 400Wh / kg. Moreover, solid-state batteries are stable under high temperature conditions, are not prone to thermal runaway, and the risk of spontaneous combustion and explosion is greatly reduced. Therefore, solid-state batteries have become an ideal object for the next generation of new energy vehicle power batteries.
[0003] Existing solid electrolytes are mainly divided into three categories, namely polymer solid electrolytes, sulfide solid electrolytes and oxide solid electrolytes. Among them, polymer solid electrolytes are composed of a polymer matrix (such as polyester, polyenzyme or polyamine) and a lithium salt (such as LiClO4, LiAsF4, LiPF6 or LiBF4); however, since ion transport in solid polymer electrolytes mainly occurs in the amorphous region and the polymer matrix has a high degree of crystallinity, this leads to a low ionic conductivity of the polymer solid electrolyte.
[0004] In order to improve the ionic conductivity of polymer solid electrolytes, some studies have been conducted to dope certain inorganic fillers in polymer solid electrolytes. However, inorganic fillers are prone to agglomeration, which leads to Li + The discontinuous and uneven channels result in limited improvement in the ionic conductivity of polymer solid electrolytes. Other studies have pointed out that although the method of doping a certain amount of liquid electrolyte into the polymer solid electrolyte can effectively improve the ionic conductivity of the polymer solid electrolyte, the risk of liquid electrolyte leakage is greatly increased due to the doping of liquid electrolyte, which is not conducive to the safety of the polymer solid electrolyte.
[0005] Therefore, providing a composite solid electrolyte with high ionic conductivity has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0006] The purpose of the present invention is to provide a composite solid electrolyte with high ionic conductivity. The composite solid electrolyte has high ionic conductivity.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] A composite solid electrolyte with high ion conductivity comprises the following raw materials in parts by mass: 4 to 8 parts of modified polyethylene oxide, 0.5 to 1.5 parts of modified LiFePO4 / C and 1 to 3 parts of molybdenum dioxide.
[0010] Furthermore, the preparation method of the modified polyethylene oxide comprises the following steps:
[0011] Polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted to obtain the modified polyethylene oxide.
[0012] Furthermore, the molecular weight of the polyethylene oxide is 300,000.
[0013] Furthermore, the molar ratio of polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile is 5:(0.1-0.5):(0.5-1.5):(1-2).
[0014] Furthermore, the reaction is specifically: reacting at 40° C. for 5 to 8 hours.
[0015] Furthermore, the preparation method of the modified LiFePO4 / C comprises the following steps:
[0016] The LiFePO4 / C is placed in a titanium sulfate solution for impregnation modification to obtain the modified LiFePO4 / C.
[0017] Furthermore, the preparation method of LiFePO4 / C comprises the following steps:
[0018] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0019] 2) The LiFePO4 / C precursor obtained in step 1) is dispersed in N,N-dimethylformamide, ball-milled for 2 hours, and calcined at 650° C. for 8 hours to obtain the LiFePO4 / C.
[0020] Furthermore, the titanium sulfate solution is a titanium sulfate solution with a volume fraction of 20%.
[0021] Furthermore, the mass volume ratio of the LiFePO4 / C and the titanium sulfate solution is 1 g:10 mL.
[0022] Furthermore, the impregnation modification is specifically: impregnation modification at 60-80° C. for 2 hours.
[0023] The second technical solution of the present invention:
[0024] The method for preparing the composite solid electrolyte with high ionic conductivity comprises the following steps:
[0025] The modified polyethylene oxide, the modified LiFePO4 / C and molybdenum dioxide are mixed and ball-milled to obtain a mixture; then the mixture is subjected to a hot pressing treatment to obtain the composite solid electrolyte with high ionic conductivity.
[0026] Furthermore, the ball milling time is 10 to 15 hours.
[0027] Furthermore, the hot pressing treatment is specifically as follows: placing the mixture in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, and after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 15 to 20 times.
[0028] The third technical solution of the present invention:
[0029] Application of the above-mentioned high ionic conductivity composite solid electrolyte in solid-state batteries.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The composite solid electrolyte with high ionic conductivity provided by the present invention has an ionic conductivity of up to 5.4×10 -4 S cm -1 , with higher ionic conductivity. DETAILED DESCRIPTION
[0032] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0033] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] In the following examples and comparative examples, unless otherwise specified, all raw materials used are commercially available, some of which can be found in Table 1;
[0038] Table 1 Raw materials and purchase channels
[0039]
[0040] A method for preparing a composite solid electrolyte with high ionic conductivity comprises the following steps:
[0041] 1. Preparation of modified polyethylene oxide:
[0042] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile being 5:(0.1-0.5):(0.5-1.5):(1-2), polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40° C. for 5-8 hours to obtain modified polyethylene oxide;
[0043] 2. Preparation of LiFePO4 / C:
[0044] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0045] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0046] 3. Preparation of modified LiFePO4 / C:
[0047] According to the mass volume ratio of LiFePO4 / C and titanium sulfate solution being 1 g:10 mL, the LiFePO4 / C obtained in step 2 is placed in a titanium sulfate solution having a volume fraction of 20%, and is immersed and modified at 60-80°C for 2 hours to obtain modified LiFePO4 / C;
[0048] 4. Preparation of composite solid electrolyte:
[0049] 1) According to the mass ratio of modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide being (4-8):(0.5-1.5):(1-3), the modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide are mixed, and ball milled for 10-15 hours to obtain a mixture;
[0050] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 15 to 20 times to obtain the composite solid electrolyte.
[0051] Example 1
[0052] A composite solid electrolyte with high ionic conductivity
[0053] 1. Preparation of modified polyethylene oxide:
[0054] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile being 5:0.1:0.5:1, polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40° C. for 5 hours to obtain modified polyethylene oxide;
[0055] 2. Preparation of LiFePO4 / C:
[0056] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0057] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0058] 3. Preparation of modified LiFePO4 / C:
[0059] According to the mass volume ratio of LiFePO4 / C and titanium sulfate solution being 1 g:10 mL, the LiFePO4 / C obtained in step 2 is placed in a titanium sulfate solution having a volume fraction of 20%, and is immersed and modified at 60°C for 2 h to obtain modified LiFePO4 / C;
[0060] 4. Preparation of composite solid electrolyte:
[0061] 1) According to the mass ratio of modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide being 4:0.5:1, the modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide are mixed, and ball milled for 10 hours to obtain a mixture;
[0062] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 15 times to obtain the composite solid electrolyte.
[0063] Example 2
[0064] A composite solid electrolyte with high ionic conductivity
[0065] 1. Preparation of modified polyethylene oxide:
[0066] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile being 5:0.4:1:1.5, polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40°C for 6 hours to obtain modified polyethylene oxide;
[0067] 2. Preparation of LiFePO4 / C:
[0068] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0069] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0070] 3. Preparation of modified LiFePO4 / C:
[0071] According to the mass volume ratio of LiFePO4 / C and titanium sulfate solution being 1 g:10 mL, the LiFePO4 / C obtained in step 2 is placed in a titanium sulfate solution having a volume fraction of 20%, and is immersed and modified at 70°C for 2 h to obtain modified LiFePO4 / C;
[0072] 4. Preparation of composite solid electrolyte:
[0073] 1) According to the mass ratio of modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide being 6:1:2, the modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide are mixed, and ball milled for 12 hours to obtain a mixture;
[0074] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 18 times to obtain the composite solid electrolyte.
[0075] Example 3
[0076] A composite solid electrolyte with high ionic conductivity
[0077] 1. Preparation of modified polyethylene oxide:
[0078] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile being 5:0.5:1.5:2, polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40°C for 8 hours to obtain modified polyethylene oxide;
[0079] 2. Preparation of LiFePO4 / C:
[0080] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0081] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0082] 3. Preparation of modified LiFePO4 / C:
[0083] According to the mass volume ratio of LiFePO4 / C and titanium sulfate solution being 1 g:10 mL, the LiFePO4 / C obtained in step 2 is placed in a titanium sulfate solution having a volume fraction of 20%, and is immersed and modified at 80°C for 2 h to obtain modified LiFePO4 / C;
[0084] 4. Preparation of composite solid electrolyte:
[0085] 1) According to the mass ratio of modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide being 8:1.5:3, the modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide are mixed, and ball milled for 15 hours to obtain a mixture;
[0086] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 20 times to obtain the composite solid electrolyte.
[0087] Comparative Example 1
[0088] A composite solid electrolyte
[0089] 1. Preparation of modified polyethylene oxide:
[0090] According to the molar ratio of polyethylene oxide, propylene carbonate and succinonitrile being 5:1:1.5, polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40° C. for 6 hours to obtain modified polyethylene oxide;
[0091] 2. Preparation of LiFePO4 / C:
[0092] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0093] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0094] 3. Preparation of modified LiFePO4 / C:
[0095] According to the mass volume ratio of LiFePO4 / C and titanium sulfate solution being 1 g:10 mL, the LiFePO4 / C obtained in step 2 is placed in a titanium sulfate solution having a volume fraction of 20%, and is immersed and modified at 70°C for 2 h to obtain modified LiFePO4 / C;
[0096] 4. Preparation of composite solid electrolyte:
[0097] 1) According to the mass ratio of modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide being 6:1:2, the modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide are mixed, and ball milled for 12 hours to obtain a mixture;
[0098] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 18 times to obtain the composite solid electrolyte.
[0099] Comparative Example 2
[0100] A composite solid electrolyte
[0101] 1. Preparation of modified polyethylene oxide:
[0102] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide and succinonitrile being 5:0.4:1.5, polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40° C. for 6 hours to obtain modified polyethylene oxide;
[0103] 2. Preparation of LiFePO4 / C:
[0104] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0105] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0106] 3. Preparation of modified LiFePO4 / C:
[0107] According to the mass volume ratio of LiFePO4 / C and titanium sulfate solution being 1 g:10 mL, the LiFePO4 / C obtained in step 2 is placed in a titanium sulfate solution having a volume fraction of 20%, and is immersed and modified at 70°C for 2 h to obtain modified LiFePO4 / C;
[0108] 4. Preparation of composite solid electrolyte:
[0109] 1) According to the mass ratio of modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide being 6:1:2, the modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide are mixed, and ball milled for 12 hours to obtain a mixture;
[0110] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 18 times to obtain the composite solid electrolyte.
[0111] Comparative Example 3
[0112] A composite solid electrolyte
[0113] 1. Preparation of modified polyethylene oxide:
[0114] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide and propylene carbonate being 5:0.4:1, polyethylene oxide, N,N-dimethylformamide and propylene carbonate are mixed and reacted at 40° C. for 6 hours to obtain modified polyethylene oxide;
[0115] 2. Preparation of LiFePO4 / C:
[0116] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0117] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0118] 3. Preparation of modified LiFePO4 / C:
[0119] According to the mass volume ratio of LiFePO4 / C and titanium sulfate solution being 1 g:10 mL, the LiFePO4 / C obtained in step 2 is placed in a titanium sulfate solution having a volume fraction of 20%, and is immersed and modified at 70°C for 2 h to obtain modified LiFePO4 / C;
[0120] 4. Preparation of composite solid electrolyte:
[0121] 1) According to the mass ratio of modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide being 6:1:2, the modified polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide are mixed, and ball milled for 12 hours to obtain a mixture;
[0122] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 18 times to obtain the composite solid electrolyte.
[0123] Comparative Example 4
[0124] A composite solid electrolyte
[0125] 1. Preparation of LiFePO4 / C:
[0126] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0127] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0128] 2. Preparation of modified LiFePO4 / C:
[0129] According to the mass volume ratio of LiFePO4 / C and titanium sulfate solution being 1 g:10 mL, the LiFePO4 / C obtained in step 2 is placed in a titanium sulfate solution having a volume fraction of 20%, and is immersed and modified at 70°C for 2 h to obtain modified LiFePO4 / C;
[0130] 3. Preparation of composite solid electrolyte:
[0131] 1) polyethylene oxide, modified LiFePO4 / C and molybdenum dioxide are mixed in a mass ratio of 6:1:2, and ball-milled for 12 hours to obtain a mixture;
[0132] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 18 times to obtain the composite solid electrolyte.
[0133] Comparative Example 5
[0134] A composite solid electrolyte
[0135] 1. Preparation of modified polyethylene oxide:
[0136] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile being 5:0.4:1:1.5, polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40°C for 6 hours to obtain modified polyethylene oxide;
[0137] 2. Preparation of LiFePO4 / C:
[0138] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0139] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0140] 3. Preparation of composite solid electrolyte:
[0141] 1) According to the mass ratio of modified polyethylene oxide, LiFePO4 / C and molybdenum dioxide being 6:1:2, the modified polyethylene oxide, LiFePO4 / C and molybdenum dioxide are mixed, and ball milled for 12 hours to obtain a mixture;
[0142] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 18 times to obtain the composite solid electrolyte.
[0143] Comparative Example 6
[0144] A composite solid electrolyte
[0145] 1. Preparation of modified polyethylene oxide:
[0146] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile being 5:0.4:1:1.5, polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40°C for 6 hours to obtain modified polyethylene oxide;
[0147] 2. Preparation of modified LiFePO4:
[0148] According to the mass volume ratio of LiFePO4 to titanium sulfate solution of 1g:10mL, LiFePO4 was placed in a titanium sulfate solution with a volume fraction of 20%, and immersed at 70°C for 2h to obtain modified LiFePO4;
[0149] 4. Preparation of composite solid electrolyte:
[0150] 1) According to the mass ratio of modified polyethylene oxide, modified LiFePO4 and molybdenum dioxide being 6:1:2, the modified polyethylene oxide, modified LiFePO4 and molybdenum dioxide are mixed, and ball milled for 12 hours to obtain a mixture;
[0151] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 18 times to obtain the composite solid electrolyte.
[0152] Comparative Example 7
[0153] A composite solid electrolyte
[0154] 1. Preparation of modified polyethylene oxide:
[0155] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile being 5:0.4:1:1.5, polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40°C for 6 hours to obtain modified polyethylene oxide;
[0156] 2. Preparation of composite solid electrolyte:
[0157] 1) According to the mass ratio of modified polyethylene oxide, LiFePO4 and molybdenum dioxide being 6:1:2, the modified polyethylene oxide, LiFePO4 and molybdenum dioxide are mixed, and ball milled for 12 hours to obtain a mixture;
[0158] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 18 times to obtain the composite solid electrolyte.
[0159] Comparative Example 8
[0160] A composite solid electrolyte
[0161] 1. Preparation of modified polyethylene oxide:
[0162] According to the molar ratio of polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile being 5:0.4:1:1.5, polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted at 40°C for 6 hours to obtain modified polyethylene oxide;
[0163] 2. Preparation of LiFePO4 / C:
[0164] 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor;
[0165] 2) dispersing the LiFePO4 / C precursor obtained in step 1) in N,N-dimethylformamide, ball milling for 2 h, and calcining at 650° C. for 8 h to obtain LiFePO4 / C;
[0166] 3. Preparation of modified LiFePO4 / C:
[0167] According to the mass volume ratio of LiFePO4 / C and titanium sulfate solution being 1 g:10 mL, the LiFePO4 / C obtained in step 2 is placed in a titanium sulfate solution having a volume fraction of 20%, and is immersed and modified at 70°C for 2 h to obtain modified LiFePO4 / C;
[0168] 4. Preparation of composite solid electrolyte:
[0169] 1) According to the mass ratio of modified polyethylene oxide to modified LiFePO4 / C being 6:1, the modified polyethylene oxide and the modified LiFePO4 / C are mixed, and ball milled for 12 hours to obtain a mixture;
[0170] 2) placing the mixture obtained in step 1) in a hot press, controlling the hot pressing temperature to 100° C., the pressure to 10 MPa, and the time to 30 min, hot pressing the mixture, after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 18 times to obtain the composite solid electrolyte.
[0171] The ion conductivity of the composite solid electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 8 was tested, and the results of the ion conductivity test are shown in Table 2;
[0172] Table 2 Ionic conductivity test results
[0173]
[0174]
[0175] From the data in Table 2, it can be seen that the ionic conductivity of the composite solid electrolyte with high ionic conductivity provided by the present invention can reach 5.4×10 -4 S cm -1 , with higher ionic conductivity; while omitting any raw material in the modified polyethylene oxide, omitting the modification of polyethylene oxide, omitting the modification of LiFePO4 / C, preparing the composite solid electrolyte with modified LiFePO4 as the raw material, preparing the composite solid electrolyte with LiFePO4 as the raw material, and omitting the addition of molybdenum dioxide will all reduce the ionic conductivity of the composite solid electrolyte to a certain extent.
[0176] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A composite solid electrolyte with high ionic conductivity, characterized in that: The composite solid electrolyte with high ionic conductivity comprises the following raw materials in parts by mass: 4 to 8 parts of modified polyethylene oxide, 0.5 to 1.5 parts of modified LiFePO4 / C and 1 to 3 parts of molybdenum dioxide.
2. A composite solid electrolyte with high ionic conductivity according to claim 1, characterized in that: The preparation method of the modified polyethylene oxide comprises the following steps: Polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile are mixed and reacted to obtain the modified polyethylene oxide.
3. A composite solid electrolyte with high ionic conductivity according to claim 2, characterized in that: The molecular weight of the polyethylene oxide is 300,000; the molar ratio of the polyethylene oxide, N,N-dimethylformamide, propylene carbonate and succinonitrile is 5:(0.1-0.5):(0.5-1.5):(1-2); the reaction is specifically: reacting at 40°C for 5-8h.
4. A composite solid electrolyte with high ionic conductivity according to claim 1, characterized in that: The preparation method of the modified LiFePO4 / C comprises the following steps: The LiFePO4 / C is placed in a titanium sulfate solution for impregnation modification to obtain the modified LiFePO4 / C.
5. A composite solid electrolyte with high ionic conductivity according to claim 4, characterized in that: The preparation method of LiFePO4 / C comprises the following steps: 1) According to the molar ratio of Fe(NO3)3·9H2O, H3PO4 and urea being 1:2:2, Fe(NO3)3·9H2O, H3PO4 and urea were mixed, reacted at 70°C for 5h, filtered, washed and dried to obtain LiFePO4 / C precursor; 2) The LiFePO4 / C precursor obtained in step 1) is dispersed in N,N-dimethylformamide, ball-milled for 2 hours, and calcined at 650° C. for 8 hours to obtain the LiFePO4 / C.
6. A composite solid electrolyte with high ionic conductivity according to claim 4, characterized in that: The titanium sulfate solution is a titanium sulfate solution with a volume fraction of 20%.
7. A composite solid electrolyte with high ionic conductivity according to claim 4, characterized in that: The mass volume ratio of the LiFePO4 / C and the titanium sulfate solution is 1 g: 10 mL; the impregnation modification is specifically: impregnation modification at 60-80°C for 2 hours.
8. A method for preparing a composite solid electrolyte with high ionic conductivity as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: The modified polyethylene oxide, the modified LiFePO4 / C and molybdenum dioxide are mixed and ball-milled to obtain a mixture; the mixture is then subjected to a hot pressing treatment to obtain the composite solid electrolyte with high ionic conductivity.
9. The preparation method according to claim 8, characterized in that: The ball milling time is 10 to 15 hours; the hot pressing treatment is specifically as follows: placing the mixture in a hot press, controlling the hot pressing temperature to 100°C, the pressure to 10MPa, and the time to 30 minutes, hot pressing the mixture, and after the hot pressing is completed, folding the mixture in half, and repeating the hot pressing 15 to 20 times.
10. Use of the composite solid electrolyte with high ionic conductivity according to any one of claims 1 to 7 in a solid-state battery.